CAPACITY BUILDING IN THE DEVELOPMENT OF A LOCAL WISDOM-BASED CREATIVE ECONOMY IN BAUBAU CITY - Asmiddin, Sri Asmidar; Mohammad Thahir Haning; Muhammad Akmal Ibrahim; Abd Haris (Gema Kampus IISIP YAPIS Biak, 2026)
This study aims to analyze capacity building in the advancement of a local wisdom–based creative economy in Baubau City, Southeast Sulawesi Province. Capacity building plays a crucial role in strengthening the capabilities of human resources, organizations, and institutions to achieve development effectiveness. Referring to the capacity building model proposed by Grindle (1997), this study focuses on three main dimensions: human resource development, organizational strengthening, and institutional reform. This research employs a qualitative approach, with data collected through in-depth interviews, observations, and document analysis involving eleven informants representing government officials, academics, creative economy actors, and cultural communities. The findings reveal that capacity building in Baubau City has not been optimally implemented. In terms of the human resource dimension, training and mentoring programs have been conducted; however, they remain uneven and lack sustainability. From an organizational perspective, Dekranasda has played an active role in fostering the creative economy, yet inter-agency coordination remains weak. Meanwhile, at the institutional level, the absence of specific regulations has resulted in sectoral and uncoordinated implementation of creative economy programs. Therefore, enhancing the competencies of creative economy actors, restructuring organizational frameworks, and establishing supportive regulatory mechanisms are necessary to ensure that the development of a local wisdom–based creative economy in Baubau City can be carried out more effectively and sustainably.